Reading the book Orphans of Eldorado and its movie adaptation - Martinez, Letícia (2020)
Milton Hatoum is recognized for writing memorial novels, structured in a fragmented and non-linear way, which can become a challenge for adaptations. However, the novella Orphans of Eldorado, although it features traces of a memorialistic narrative, was adapted into a film in 2015, by the director Guilherme Coelho. This article proposes a discussion about hypotextuality (source/earlier text) and hypertextuality (later text), by using the theories and concepts developed by Gérard Genette, Linda Hutcheon and Robert Stam in order to develop an analysis on the adaptation of the novella to the cinema.